Wind tunnel experiments of bending-torsion and body-freedom flutter on flying wing unmanned aerial vehicles - Ang, Elijah Hao Wei (2024)
Wind tunnel experiments are performed on a flying wing model to investigate the effects of key design parameters and their cross-interactions on the flutter speed and frequency for bending-torsion flutter (BTF) and body-freedom flutter (BFF). These design parameters include wing sweep angle, mass of tip weights, and location of weights along the wingspan. A slider and rail setup for BFF is designed to enable rigid-body pitching and plunging degrees-of-freedom, while a custom fixed clamp is used to perform the BTF experiments. BTF and BFF experiences different dominant modes while undergoing flutter, with the former's dominant mode being torsion and the latter being the rigid-body short-period mode. For BTF, flutter speeds increase as weights are moved towards the wingtip or increasing tip weights, which increases the inertia of the system to enhance stability. The effect is opposite for BFF as the movement of weights outboard or increase of tip weights result in a rearwards shift of the centre of gravity that destabilises the system. In general, a higher sweep angle leads to increased sensitivity of flutter speeds to changes in mass of tip weights or changes to spanwise location of the weights. The findings from this study provide insights to the design of flying wing unmanned aerial vehicles for increased stability margins.